Strategic geographies: Dialogues, totality and the modern prince - Halvorsen, Sam (Progress in human geography, 2025)
Strategy is a pervasive yet undertheorised concept in geography. While spatial strategies have been analysed across sub-disciplinary areas, and ‘strategic interventions’ invoked in debates, the term remains poorly defined and often conflated with tactics. The core contribution of the paper is to develop strategic geographies as a heuristic for understanding geography’s role in crafting an engaged and collective project of social transformation. It does so by developing the conceptual triad of dialogues , totality , and the modern Prince , to clarify the relation of tactics to strategy, build bridges across fragmented debates, and link them outward to the practice of engaged scholarship.